2019
DOI: 10.2298/tsci180503007u
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of distance between v-gutters on flame stabilization and NOx emissions

Abstract: Blow-off performance and NO x emissions of the propane and air mixture in a rectangular combustion chamber with bluff bodies were investigated experimentally and numerically. The effects of distance between bluff bodies on NO x emissions, the blow-off limit, and exhaust gas temperature were examined. It was observed that NO x emissions are highly dependent on distance between V-gutters. The re-circulation zone behind the bluff body expands in width based on the decrease of distance between V-gutters, and expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Simulations performed in [15] with a triangular-shaped bluff body (with slits on both sides) and based on experimental data obtained [8] indicate that the increasing in the angle at the corner vertex leads to increased flame stabilization. Similar results have been reported in [16,17].…”
Section: State-of-the-art: a Brief Overviewsupporting
confidence: 91%
See 2 more Smart Citations
“…Simulations performed in [15] with a triangular-shaped bluff body (with slits on both sides) and based on experimental data obtained [8] indicate that the increasing in the angle at the corner vertex leads to increased flame stabilization. Similar results have been reported in [16,17].…”
Section: State-of-the-art: a Brief Overviewsupporting
confidence: 91%
“…The main scientific and technical challenges address the increases in the operating efficiencies of the gas turbine bases combustion devices inasmuch as decreasing the harmful emissions is a principle task in the new century. Considering technical and economic perspectives it is acceptable to use bluff bodies or their combinations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In this context, a considerable advantage of burners based on bluff bodies is that they can operate with various kinds of --------------fuels in a broad range of densities and viscosities such as heavy petroleum-based gases or light natural gases or various gas mixtures with hydrogen [6].…”
Section: State-of-the-art: a Brief Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work mainly concerns the numerical simulation of the phenomenon of turbulent combustion, in a non-premixed flame of the H2-Air type. The aim is to produce a numerical investigation of non-polluting combustion and giving rise to very high temperatures (of the order of 2000 K) [17]. The studied configuration is composed of two coaxial axis-symmetric jets, such as can be found in diffusion burners.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the main reasons for the formation of nitrogen oxides in various devices and the prospects for the development of the power industry showed that traditional methods of fuel combustion do not provide the required parameters. Improving the efficiency of fuel combustion can be obtained by using microflame combustion [1][2][3].…”
Section: Introductionmentioning
confidence: 99%